MODEL DINAMIS SUPPLY CHAIN BERAS BERKELANJUTAN DALAM UPAYA KETAHANAN PANGAN NASIONAL - Akhmad Mahbubi (School of Business, Bogor Agricultural University (SB-IPB), 2013)
ABSTRACTThis study was aimed to 1) identify the basic system of rice supply chain, 2) design a conceptual system and formulate a model of rice supply chain to achieve rice food security and 3) identify the sustainability behavior of the rice supply chain systems for the next 30 years from the aspects of economical revenue, social welfare and environment. Dynamic model was used to analyze the data. Referring to a variety of technical indicators achievement in the blueprint of national food security, several policy scenarios were used in the analysis of the behavior of rice supply chain systems until 2042 in economical revenue, social welfare and the environment aspects. The results of this study showed that the self-sufficiency of rice will continue until 2042 (the end of the study’s simulation). It also showed that in the long run, national rice food security will be disrupted if the government does not stop the conversion of agricultural land. Therefore, the government needs to issue a policy related to the conversion of agricultural land, especially paddy fields for infrastructure development.Keywords: rice, sustainable, food security, dynamic models, supply chainABSTRAKTujuan Penelitian adalah 1) mengidentifikasi sistem dasar supply chain beras, 2) menyusun konseptual sistem dan formulasi model supply chain beras untuk pencapaian ketahanan pangan nasional, serta 3) mengetahui perilaku sistem supply chain beras untuk 30 tahun kedepan tetap berkelanjutan dilihat dari aspek pendapatan ekonomi, sosial dan lingkungan. Analisis data menggunakan model dinamis. Beberapa skenario dalam analisis perilaku supply chain beras sampai tahun 2042 dilihat dari aspek pendapatan ekonomi, sosial dan lingkungan mengacu pada indikator pencapaian dalam blue print ketahanan pangan nasional. Hasil penelitian ini, swasembada pangan beras akan berkelanjutan sampai 2042 (akhir dari simulasi penelitian ini). Dalam jangka panjang, ketahanan pangan beras nasional akan terganggu jika pemerintah tidak menghentikan konversi lahan pertanian. Oleh karena itu, pemerintah perlu mengeluarkan kebijakan penghentian atau pengetatan konversi lahan pertanian khususnya lahan sawah untuk pembangunan infrastruktur.Kata kunci: beras, berkelanjutan, ketahanan pangan, model dinamis, supply chain